Analisis Bibliometrik In Find Research Gap Bidang Ilmu Keperawatan Menggunakan Aplikasi Publish or Perish dan Vosviewer di Indonesia - Thamrin Hasan; Yurnalis (Jurnal Gema Pustakawan, 2024)
This research aims to analyze current research trends in the field of homicide in Indonesia, identify the most studied research topics, and find research gaps that can be studied further. This research uses a bibliometric method with data from Google Scholar for the 2018-2022 period which was harvested via the Publish or Perish application. Bibliometric analysis was carried out based on six characteristics: (1) article publication trends, (2) journals that published the most articles, (3) most cited articles, (4) frequently used keywords, (5) most frequently used author's institutions productive, and (6) visualization of analysis results using VOSviewer. The research results show: 1) Journal of Mental Nursing Science is the most active journal related to research in the field of poisoning in Indonesia in 2018-2022. 2) Kedal College of Health Sciences (STIKES) is the most active research institution with many articles cited. 3) Livana, P.H. the most active author and contributed greatly to homicide research. 4) The most cited article is the result of Anung Ahadi Pradana's research. 5) Research topics that are widely discussed include maintenance, workload, critical thinking, fatigue, caring, intervention, leadership, job satisfaction, patient satisfaction, nurse performance, service quality, training, care services, nurse experience, and nurse knowledge . 6) Research topics that are gaps and have the potential for further research include the role of the family, relaxation, schizophrenia, violence, hemodialysis, self-efficacy, stroke, breast milk production, adolescent sexual behavior, anxiety, depression, self-concept, obesity, and contraception. It can be concluded that this research succeeded in finding research gaps in the field of bleeding in Indonesia can be used as a reference for further research.